The Effectiveness Of The Cone Drill Training Method To Increase Speed In Futsal Athletes At Mts Darut Taqwa 02 Purwosari Pasuruan - Muhammad Fajrul Falah; Wiwik Kusmawati (Jurnal Pendidikan Jasmani (JPJ), 2026)
The decline in performance and the decline in speed ability are the main factors for the MTs Darut Taqwa 02 Purwosari Pasuruan futsal team. Speed ​​is an important biomotor component in futsal that requires fast rotation on the futsal field. Purpose: This study aims to determine the effectiveness of the cone drill training method with X-Pattern Multiskill variations to increase speed with a 20-meter sprint test on futsal players. Method: This type of research uses an experiment with a one-group pretest-posttest design. The research sample consisted of 10 students selected using a purposive sampling technique. The instrument used was a 20-meter sprint test. Data were analyzed using descriptive tests and Paired Sample T-Test tests with the help of SPSS 25. Results: The results showed a decrease in the average travel time from 3.68 seconds in the pretest to 3.41 seconds in the post-test. The results of the Paired Sample T-Test obtained a t-count value of 16.082 > t-table 2.262 and a significance value (Sig. 2-tailed) of 0.000 < 0.05. Conclusion: It can be concluded that cone drill training is effective and can significantly increase the speed of futsal players at MTs Darut Taqwa 02 Purwosari Pasuruan. This increase is driven by the adaptation of the neuromuscular system and synchronization of motor units through structured training patterns.